Molecular phylogeny and divergence of major clades in the Puntius complex (Teleostei: Cypriniformes). (16th August 2020) - Ren, Qiu; Yang, Lei; Chang, Chia‐Hao; Mayden, Richard L.
Abstract: Puntius sensu lato ( s.l .) was one of the most speciose genera in the family Cyprinidae. There are around 120 valid species widely distributed in South‐East and South Asia, and South China. Puntius has long been known as an artificial assemblage and 'catch‐all' genus in which a large number of small, unrelated cyprinids have been placed. With new species and genera being described each year, obtaining detailed knowledge of the phylogenetic relationships of this complex is critically important in the assessment of a natural classification. In the present study, two mitochondrial and four nuclear genes were used to examine the inter‐specific and inter‐generic relationships of the Puntius complex and to test the monophyly of the current genera. Divergence time analysis was performed to explore the origin, evolution, and divergence of major clades in Puntius s.l . Results revealed that the genera Puntius seusu stricto ( s.s .), Systomus, Pethia, Haludaria, Desmopuntius and Puntigrus were monophyletic with high support. However, monophyly of Barbodes, Striuntius and Sahyadria was not supported. Dawkinsia and Sahyadria formed a highly supported clade. Puntius semifasciolatus and P. snyderi from South China and Taiwan represent a new lineage. Inferences from divergence time analysis indicated that Puntius s.l . likely dated to early Miocene. Major clades in Puntius s.l . diverged during Miocene as well.